FACTORS FOR DE-SELECTION OF POTENTIAL CANDIDATES FOR LIVER DONOR LIVER TRANPLANT IN A TETIARY CARE HOSPITAL - Anum Abbas; Rabia Tariq; Aimen Abbas; Ehtesham Haider; Farrukh Saeed (Pakistan Armed Forces Medical Journal, 2020)
Objective: To look for factors responsible for de-selection of patients for live donor liver transplantat tertiary care hospital.